2007
DOI: 10.1124/jpet.107.125567
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Large-Conductance Calcium-Activated Potassium Channels by Puerarin: The Underlying Mechanism of Puerarin-Mediated Vasodilation

Abstract: Puerarin is the main isoflavone found in Pueraria lobata (Willd) Ohwi, which has been used in therapy for various cardiovascular diseases. The present study examined the effects of puerarin on the large-conductance voltage-and Ca 2ϩ -activated potassium (BK Ca ) channel and on rat thoracic aortas. BK Ca channels encoded with either ␣ (BK-␣) or ␣/␤ subunits (BK-␣ϩ␤1) were heterologously expressed in Xenopus oocytes or human embryonic kidney 293 cells. The activities of BK Ca channels were measured using excised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 23 publications
0
47
0
Order By: Relevance
“…Xu et al reported that kaempferol exerts part of its vasodilatory activity via activation of BK Ca channels [31]. Similar effects have been shown for the isoflavone puerarin [32]. Dioclein, a flavonoid isolated from the root of Dioclea grandiflora, a legume of the native Americans, causes hypotension in normotensive rats [33].…”
Section: Activation Of the Vascular Calcium Activated Potassium Channmentioning
confidence: 75%
“…Xu et al reported that kaempferol exerts part of its vasodilatory activity via activation of BK Ca channels [31]. Similar effects have been shown for the isoflavone puerarin [32]. Dioclein, a flavonoid isolated from the root of Dioclea grandiflora, a legume of the native Americans, causes hypotension in normotensive rats [33].…”
Section: Activation Of the Vascular Calcium Activated Potassium Channmentioning
confidence: 75%
“…Daidzein was also found to reduce the endothelial release of prostaglandin H 2 , a cyclooxygenase-derived vasoconstrictor (Vera et al, 2005). Puerarin, one of the active components of Gegen, was found to be involved in activating the large-conductance calcium-activated potassium channels (Sun et al, 2007). Despite evidence showing the individual vasodilative effect of Danshen and Gegen, the combined effect of DG on aorta was yet to be studied.…”
Section: Discussionmentioning
confidence: 96%
“…Besides, tanshinone II A , a lipophilic active ingredient of Danshen, could induce relaxation on rat coronary arteries and aorta through nitric oxide (NO)-mediated vasodilation (Kim et al, 2007;Wu et al, 2009) and was found to be K ATP channel-related . For Gegen, its active component daidzein, was shown to improve endothelial function in several studies (Mishra et al, 2000;Colacurci et al, 2005) and it induced vasodilation through NO-mediated mechanism (Mishra et al, 2000;Vera et al, 2005), and large-conductance calcium-activated potassium channels (Sun et al, 2007;Zhao et al, 2010), Kir channels Further investigations of the involvement of (a) inward rectifier potassium channels (BaCl2); (b) voltage-dependent potassium channels (4-AP); (c) ATP-sensitive potassium channels (glibenclamide) and (d) large conductance calcium-activated potassium channels (iberiotoxin, IbTX) in DG extract-induced relaxations of (a, b, and d) U46619 or (c) phenylephrine-precontracted aorta rings. The results were expressed as mean ± SEM (n = 6-8), with *p < 0.05 and **p < 0.01, using one-way ANOVA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2) Its pharmacological effects are due to the presence of isoflavonoids, which include puerarin, daidzin, and other related metabolites. Puerarin exhibits diverse medicinal properties including hypotensive, 3) hypolipidemic, 4) hypoglycemic, 5) anti-oxidant, 6) anti-ischaemia, 7) vasodilation 8) and estrogen-like effects. 9) As an isoflavonoid, the biosynthesis of puerarin should derive from phenylpropanoid metabolism, in which the enzymes in the early steps such as phenylalanine ammonia lyase (PAL), cinnamate 4-hydroxylase (C4H), 4-coumarate : coenzyme A ligase (4CL), chalcone synthase (CHS), chalcone reductase (CHR), and chalcone isomerase (CHI) are conserved in many plant species.…”
mentioning
confidence: 99%